Mobile Social Signal Processing First International Workshop, MSSP 2010, Lisbon, Portugal, September 7, 2010, Invited Papers - Murray-Smith, Roderick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book contains papers invited after the First International Workshop on Mobile Social Signal Processing, MSSP 2010, held in Lisbon, Portugal, in September 2010. The 9 revised papers included in this volume represent the diversity of two fields of research, Mobile HCI and Social Signal Processing, and areas of overlap. They cover a wide range of topics spanning from approaches for effective interaction with mobile and wearable devices to modelling, analysis and synthesis of nonverbal behaviour in human-human and human-machine interactions.
Mobile Phones and Social Signal Processing for Analysis and Understanding of Dyadic Conversations -- Turns Analysis for Automatic Role Recognition -- Speaker Diarization of Multi-party Conversations Using Participants Role Information: Political Debates and Professional Meetings -- Invisible, Passive, Continuous and Multimodal Authentication -- The Metaphysics of Communications Overload -- Capturing Performative Actions for Interaction and Social Awareness -- Negotiation Models for Mobile Tactile Interaction -- Direct Tactile Coupling of Mobile Phones with the feel abuzz System -- A Multimodal Contact List to Enhance Remote Communication.
Keywords: Computer science; Data mining; Multimedia systems; Computer Science; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery; Multimedia Information Systems